Profil GCMS Senyawa Kimia Ekstrak Metanol Isolat Cendawan Entomopatogen Beauveria Bassiana Dan Akar Cabai Sebagai Pemacu Pertumbuhan Cabai - Saragih, Magdalena; Trizelia, Trizelia; Nurbailis, Nurbailis; Yusniwati, Yusniwati (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
The aim of this study was to identify the chemical compound methanol extract of entomopathogenic fungus Beauveria bassiana from insect walang sangit and the chemical compound roots of red chili plants that were able to stimulate the growth of chilli plants after being applied with entomopathogenic fungus   B. bassiana through seed immersion inoculation using GCMS method. The chemical compound identified as a growth booster in   B. bassiana fungus isolates from the insect walang sangit is an Acetic acid Ethanoic acid Ethylic acid Glacial acetic acid CH3COOH, Hexadecanoic acid, methyl ester (CAS) Methylpalmitate Uniphat A60, n-Hexadecanoic acid Hexadecanoic acid n-Hexadecoic acid Palmitic acid, Dianhydromannitol and Ergosta-5,7,22-trien-3-ol, (3.beta., 22E) - (CAS) Ergosterol (CAS), while the chili root contains Acetic acid Ethanoic acid Ethylic acid Glacials acetic acid CH3COOH, Hexadecanoic acid, methyl ester (CAS) Methyl palmitate Uniphat A60, n -Hexadecanoic acid Hexadecanoic acid Palmitic acid, 8, 11- octadecadienoic acid, methyl ester (CAS) METHYL 8, 11-OCTADECADIENOATE, (23S)-ethylcholest-5-en-3.beta.-ol.s It can be concluded that some of the chemical compounds in methanol extracts identified in chili roots have similarities with chemical compounds that exist in   B. bassiana entomopathogenic fungus which are potential as stimulers of chili plant growth